2008
DOI: 10.3923/pjbs.2008.1940.1944
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility Pattern of Microorganisms Involved in the Pathogenesis of Surgical Site Infection (SSI); A 1 Year of Surveillance

Abstract: The aim of this study is to identify the antibiotic sensitivity pattern of pathogens involved in the process of surgical site infection, in surgical wards. Changes made in the pattern of antibiotic use will result in different microorganism susceptibility patterns, which needs correct determination for precise empiric antibiotic therapy. One thousand patients (62% men and 38% women, 18- 74-years-old, with mean age 43 +/- 8)) who underwent surgical treatment, in Alzahra University Hospital, Isfahan University o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
5
5
0
Order By: Relevance
“…All of the S. aureus isolates in our study showed 100% susceptibility to vancomycin. This pattern is the same as the findings of other Iranian studies (22,(33)(34)(35)(36).…”
Section: Discussionsupporting
confidence: 92%
“…All of the S. aureus isolates in our study showed 100% susceptibility to vancomycin. This pattern is the same as the findings of other Iranian studies (22,(33)(34)(35)(36).…”
Section: Discussionsupporting
confidence: 92%
“…(18.1%) and E. coli (16.9%) were the 2 nd and 3 rd most frequent isolates in our study which is consistent with the report of Khorvash et al (2008) from Iran. A Nigerian study indicated Klebsiella spp.…”
Section: Bacterial Isolatessupporting
confidence: 82%
“…The bacteria isolated in our study were commonly associated with surgical wound infections in Ethiopia and elsewhere (Ahmed et al, 2007;Tekie, 2008;Shanthi et al, 2012;Rao et al, 2013). Similar to our observation (25.4%) S. aureus was reported to be the most dominant isolate from surgical wound infections representing 25-45.1% of the total isolates (Ahmed et al, 2007;Anguzu and Olila, 2007;Khorvash et al, 2008;Tekie, 2008;Shanthi et al, 2012). The high prevalence of S. aureus infection may be partly explained by the presence of these bacteria in the nose, skin and intestinal tract of human beings (Vandepitte et al, 2003).…”
Section: Bacterial Isolatessupporting
confidence: 78%
“…13 In another study conducted by Shafqat et al, have shown E. coli (29%), as the major pathogen associated with SSI followed by Pseudomonas (23%), Klebsiella (19%), Proteus(5%), Citrobacter (2.5%) and Staphylococcus aureus (14.5%). 17 Various studies have also reported the higher percentages of gram positive organism particularly Staphylococcus aureus, associated with surgical site infection. [18][19] In present study coagulase-negative Staphylococi is also reported as a third major causative agent.…”
Section: Discussionmentioning
confidence: 99%